Tunisian hypersaline sediments to set up suitable halotolerant microbial bioanodes for electrostimulated biodegradation of thiabendazole - Saidi, Nesrine; Erable, Benjamin; Saadaoui, Sirine; Driouech, Rim; Zaouak, Amira; Jelassi, Haikel; Neifar, Mohamed; Masmoudi, Ahmed Slaheddine; Cherif, Ameur; Chouchane, Habib (Frontiers in Energy Research, 2022)
This study investigated for the first time the performance of microbial halotolerant bioanodes designed from two Tunisian Hypersaline Sediments (THS) for simultaneous electrostimulated biodegradation of synthetic fruit packaging wastewater containing thiabendazole (TBZ), and recovery of an anodic current signal. Halotolerant bioanodes formation has been conducted on 6 cm2 carbon felt electrodes polarized at -0.1Vvs Saturated Calomel Electrode (SCE), inoculated with 80 % (v:v) of synthetic wastewater containing 50 ppm of irradiated or not irradiated TBZ and 20 % (v:v) of THS for a period of 7 days. Microbial bioanodes, and the corresponding anolytes, i.e., synthetic wastewater, were studied comparatively by electrochemical, microscopic, spectroscopic, molecular and microbial ecology tools. Despite the low maximum current densities recorded in the 50 ppm TBZ runs (3.66 mA/m2), more than 80% of the TBZ was degraded when non-irradiated TBZ (nTBZ) was used as the sole carbon energy by the microorganisms. Nevertheless, the degradation in the presence of irradiated TBZ (iTBZ) was greatly reduced by increasing the irradiation dose with maximum current density of 0.95 mA/m2 and a degradation rate less than 50% of iTBZ. In addition, chemical changes were observed in TBZ as a result of gamma irradiation and bioelectrochemical degradation. FT-IR and UV-Vis techniques confirmed the degradation of TBZ structural bonds producing novel functional groups. Culture-dependent approach and 16S ribosomal RNA sequencing demonstrated that bacterial community of halotolerant bioanodes formed with nTBZ were dominated by Proteobacteria (75%) and Firmicutes (25%). At species level, enrichment of Halomonas smyrnensis, Halomonas halophila, Halomonas salina, Halomonasor ganivorans and Halomonas koreensis on carbon felt electrodes were correlated with maximal current production and nTBZ degradation. As a result, THS halotolerant bacteria, and specifically those from Chott El Djerid (CJ) site certainly have well established application for the electrostimulated microbial biodegradation of fungicide in the real fruit and vegetable processing industries.